The intentionality between phenomenolgy and the ordinary language philosophy in “Edmund Huserl”and “John Searl” view: القصدية بين الفينومينولوجيا وفلسفة اللغة العادية عند ادموند هوسرل وجون سيرل - Boubellouta , Hocine; Souilah , Hichem (Maalim, 2026)
The intentionality is the core concept in both phenomenology and ordinary language philosophy, being as the feature associated with the mind by directing it towards a certain object. However, phenomenology and ordinary language philosophy differ in the methodology of each theory. "Husserl" who is considered as the pioneer of phenomenology, relates intentionality with consciousness, and according to him it is the consciousness which directs towards the intended or perceivable subject. And accordingly, Husserl views that all the conscious states are intentional, and he focused in his methodology on the structure of intentionality by dividing it to: noesis and noema, and he set his own methodology for intentionality and he named it ephoché or suspending the judgment. On the other hand, "John Searl" views that the intentionality, within the ordinary philosophy of language, as a mental feature which directs mental states towards subjects in the external world or by representing it. Searl indicated that the main features of intentionality are the authentic and the derived intentionality in a way that linguistic intentionality is derived from mental intentionality. In addition to that, Searl tried to find the relation between individual and collective intentionality.